Serologic and Genomic Investigation of West Nile Virus in Kosovo - Petra Emmerich; Xhevat Jakupi; Kurtesh Sherifi; Shemsedin Dreshaj; Ariana Kalaveshi; Christoph Hemmer; Donjeta Pllana Hajdari; Ronald von Possel; Dániel Cadar; Alexandru Tomazatos (Viruses, 2023)
The prevalence of West Nile virus (WNV) is increasing across Europe, with cases emerging in previously unaffected countries. Kosovo is situated in a WNV-endemic region where the seroepidemiological data on WNV in humans remains absent. To address this issue, we have conducted a seroepidemiological investigation of 453 randomly selected sera from a hospital in Kosovo, revealing a 1.55% anti-WNV IgG seroprevalence. Comparative and phylogeographic analyses of the WNV genomes obtained by sequencing archived samples from patients with West Nile fever indicate at least two recent and distinct introductions of WNV lineage 2 into Kosovo from neighboring countries. These findings confirm the eco-epidemiological status of WNV in southeast Europe, where long- and short-range dispersion of lineage 2 strains contributes to a wider circulation via central Europe. Our results suggest an increasing risk for WNV spreading in Kosovo, underscoring the need for an integrated national surveillance program targeting vectors and avian populations for early epidemic detection, as well as the screening of blood donors to gauge the impact of virus circulation on the human population.